INOVASI SABERMINPRO (SATU BERKAS MINIMAL EMPAT PRODUK) DALAM PELAYANAN ADMINISTRASI KEPENDUDUKAN DI KABUPATEN PELALAWAN - Angga Refranda; Geovani Meiwanda (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
The Saberminpro innovation is a step forward made by the Pelalawan Regency Population and Civil Registration Service which aims to improve the civil registration of Pangkalan Kerinci District. With the presence of innovations that have been formulated by the Department of Population and Civil Registry of Pelalawan Regency, it can make it easier for the community to manage and in particular to provide improvements in population administration services in Sei Kijang District. The purpose of this study is to determine how innovation activities have been carried out and to find out what are the inhibiting factors of saberminpro innovation. This research uses interactive analysis techniques with qualitative research types using a descriptive approach and the required data both primary data and secondary data obtained through observation, interviews, and documentation then analyzed based on research problems. The results of this study indicate that: first, Saberminpro's innovation has not run optimally. Second, the inhibiting factors are in addition to the pandemic factor, lack of funds, facilities and infrastructure, lack of human resources, and lack of public awareness of the importance of population administration. Keywords: Innovation, Saberminpro, Population Administrati